2020
DOI: 10.3389/fnins.2020.00817
|View full text |Cite
|
Sign up to set email alerts
|

Rofecoxib Attenuates the Pathogenesis of Amyotrophic Lateral Sclerosis by Alleviating Cyclooxygenase-2-Mediated Mechanisms

Abstract: Cyclooxygenase-2 (COX-2) is reported to be activated during the course of amyotrophic lateral sclerosis (ALS) development and progression. However, the roles of COX-2 in aggravating ALS and the underlying mechanism have been largely overlooked. To reveal the mechanisms, the canonical SOD1 G93A mouse model was used as an experimental model for ALS in the current study. In addition, a specific inhibitor of COX-2 activity, rofecoxib, was orally administered to SOD1 G93A mice. With this in vivo approach, we reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Ozone could activate NF-κB and phosphatases [ 77 ], and ozone-driven cellular oxidation has been linked to fatty acid oxidation, acting as a signal traducer for Nrf2/Keap1/ARE system activation with crosstalk of Nrf2/NF-kB and AMPK/FOXO/mTOR/Sir1 pathway, which shifted cytokine activation from pro-inflammatory to anti-inflammatory and immunoregulatory effects on intestinal microbiota and regulatory T lymphocytes [ 78 ]. Activation of astrocytes and microglia cause high expression of IL-1β, COX-2, and TNF-α at the onset and during the progression of ALS in SOD1 G93A mice, and that treatment with non-steroidal anti-inflammatory drugs (NSAIDs), rofecoxib or celecoxib, markedly inhibited the expression of COX-2 [ 68 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ozone could activate NF-κB and phosphatases [ 77 ], and ozone-driven cellular oxidation has been linked to fatty acid oxidation, acting as a signal traducer for Nrf2/Keap1/ARE system activation with crosstalk of Nrf2/NF-kB and AMPK/FOXO/mTOR/Sir1 pathway, which shifted cytokine activation from pro-inflammatory to anti-inflammatory and immunoregulatory effects on intestinal microbiota and regulatory T lymphocytes [ 78 ]. Activation of astrocytes and microglia cause high expression of IL-1β, COX-2, and TNF-α at the onset and during the progression of ALS in SOD1 G93A mice, and that treatment with non-steroidal anti-inflammatory drugs (NSAIDs), rofecoxib or celecoxib, markedly inhibited the expression of COX-2 [ 68 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human erythropoietin has also been reported to prolong the life span and protect the motor neurons of G93A mice [ 40 ]. Moreover, rofecoxib, an anti-inflammatory drug, has been reported to decrease the expression of TNF-α and IL-1β in the spinal cord and to prolong survival in G93A mice [ 41 ], suggesting that it may be important to reduce pro-inflammatory cytokines in ALS therapy. Consistent with the effects of erythropoietin and rofecoxib, we found that MBP selectively suppressed the upregulation of pro-inflammatory cytokines with no influence on anti-inflammatory cytokine expression in the spinal cord of G93A mice at an early symptomatic stage ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of PGE2 in the CSF of most ALS patients are elevated 10-fold [128][129][130][131][132]. Cyclooxygenase 2 (COX2) catalyzes the conversion of arachidonic acid to PGE2; thus, blocking COX2 specifically with celecoxib or rofecoxib may slow down the development and progression of ALS [133,134].…”
Section: Fatty Acidsmentioning
confidence: 99%